Health risk assessment induced by chloroform content of the drinking water in Iran: systematic review. (2nd October 2017) - Fakhri, Yadolah; Mohseni-Bandpei, Anoushiravan; Oliveri Conti, Gea; Keramati, Hassan; Zandsalimi, Yahya; Amanidaz, Nazak; Hosseini Pouya, Rokhsane; Moradi, Bigard; Bahmani, Zohreh; Rasouli Amirhajeloo, Leila; Baninameh, Zahra
Abstract: Long-term intake of water with high content of trihalomethanes (THMs) such as chloroform (CHCl3 ) is hazardous for human health. Some studies have shown that clinical effects of THMs in drinking water may be yet observed to doses lower to standard limit. In our study, we performed a meta-analysis to assess both the mean concentration of CHCl3 in Iranian drinking water and the relative health effects by long-term exposure to safe dose of CHCl3 in the male and female age groups and in female categories. We applied the Target Hazard Quotient (THQ) for the evaluation of the noncarcinogenic risk of CHCl3 . Meta-analysis (14 studies) showed that the average concentration of CHCl3 was 24 µg/l (95%CI:18.1–30.1 µg/l), I 2 = 99.88, p < .001. Minimum and maximum concentrations of CHCl3 was related to Mashhad (3.5 ± 0.5 µg/l) and Mazandaran (57.3 ± 13.1 µg/l) province, respectively. The average concentration of CHCl3 in the all studied provinces was lower than USEPA (70 µg/l) and national standard limits (200 µg/l). The minimum and maximum THQ was related to <0.5 and 15–19 years age groups in both the males and females. The rank order of THQ in the female categories was females aging 15–44 (0.074)> non-pregnant and non-lactating females age 4–15 (0.071) > pregnant (0.071) > lactating (0.043). The THQ in the females was higher than males, non-significantly ( p >.05). Except Mazandaran province, in other provinces both males and females, for all age groups, were not exposed to significant risks by non-carcinogenic exposure of CHCl3 in drinking water (THQ <1).